Estudio de viabilidad para la creación de un modelo de outsourcing para la tercerización en nómina y contratación de personal en la upz de toberín, en la ciudad de Bogotá - Colombia (2022)
At present, it has been possible to demonstrate how the backbone of any company is focused on its good administration, and how having a good administration of the areas manages to lead the company to growth, which leads us to observe that, in the areas of Human Management, serious shortcomings are being evidenced that affect the performance of this area and therefore, being an area of supreme importance in the company, it ends up giving us instability with respect to the company's employees, the mistakes made in the area of Human Management, leads to the processes and tasks that are carried out, being processes and tasks that are exhausting and overwhelming for the people in charge of them.